Which personnel measures are effective in increasing productivity of old workers? - Christian Göbel; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
In this study, we investigate the effect of five specific human resource measures for old employees (SMOE) on their relative productivity. Despite the fact that SMOE are applied in the majority of establishments, this is the first representative study on the effectiveness of these measures. We find that the relative productivity contributions of old workers are significantly higher in establishments that provide either specific equipment of work places or age-specific jobs for old workers. In establishments that apply mixed-age working teams the productivity contributions of old and of young employees are significantly higher than in establishments without this measure. Working time reductions and specific training for old employees are not associated with higher relative productivity of these employees. Our paper provides a joint explanation for two recent findings, the only modest decline of the productivity contributions of old workers and the high variance for estimates of age-productivity profiles.
Keywords: J11; J14; J21; 330; ageing workforce; age-productivity-profile; personnel management; HRM; Arbeitskräfte; Altersgruppe; Arbeitsproduktivität; Ältere Arbeitskräfte; Personalmanagement; Deutschland